Features of influence of ultrasound on Toxocara canis (Werner, 1782) eggs - Yu. Yu. Masalkova (Российский паразитологический журнал, 2016)
The survival of Toxocara canis eggs at different stages at influence of ultra- sonic field of different power is studied. Higher stability of T. canis eggs at a stage of an invasive larva to ultrasound influence is established. Ultrasound can be used for a disinvasion of laboratory glassware, tools, water and the dry rest on treatment facilities